Payments for ecosystem services and the fatal attraction of win‐win solutions. Issue 4 (23rd January 2013) - Muradian, R.; Arsel, M.; Pellegrini, L.; Adaman, F.; Aguilar, B.; Agarwal, B.; Corbera, E.; Ezzine de Blas, D.; Farley, J.; Froger, G.; Garcia‐Frapolli, E.; Gómez‐Baggethun, E.; et al.
Abstract In this commentary we critically discuss the suitability of payments for ecosystem services and the most important challenges they face. While such instruments can play a role in improving environmental governance, we argue that over‐reliance on payments as win‐win solutions might lead to ineffective outcomes, similar to earlier experience with integrated conservation and development projects. Our objective is to raise awareness, particularly among policy makers and practitioners, about the limitations of such instruments and to encourage a dialogue about the policy contexts in which they might be appropriate.